2007
DOI: 10.1007/s00251-007-0256-0
|View full text |Cite
|
Sign up to set email alerts
|

Natural cathepsin E deficiency in the immune system of C57BL/6J mice

Abstract: Cathepsin E is an aspartic endosomal proteinase, expressed at high levels in some epithelial and haemopoetic cells. The enzyme has been implicated in a variety of functions, including antigen processing. This study documents strain-specific variation in expression of cathepsin E in mice. The levels of cathepsin E protein and message are profoundly decreased in haemopoetic cells from C57BL/6J mice, compared to levels in 129S2/Sv or Balb/c. The deficiency is cell-type-specific, as protein levels in gut are not a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
23
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 22 publications
5
23
0
Order By: Relevance
“…Real-time PCR analysis of the expression of different cysteine and aspartic cathepsins in isolated lung DCs of naive C57/BL6 mice showed a lower content of Ctse transcripts (2.98 × 10 5 mol/l), compared to transcripts of cathepsins S, D and B (6.37 × 10 8 mol/l, 3.24 × 10 8 mol/l, 2.87 × 10 8 mol/l). It was also reported that there was a natural Ctse deficiency in the immune system of C57/BL6 mice [42]. Our real-time PCR results support these findings.…”
Section: Discussionsupporting
confidence: 82%
“…Real-time PCR analysis of the expression of different cysteine and aspartic cathepsins in isolated lung DCs of naive C57/BL6 mice showed a lower content of Ctse transcripts (2.98 × 10 5 mol/l), compared to transcripts of cathepsins S, D and B (6.37 × 10 8 mol/l, 3.24 × 10 8 mol/l, 2.87 × 10 8 mol/l). It was also reported that there was a natural Ctse deficiency in the immune system of C57/BL6 mice [42]. Our real-time PCR results support these findings.…”
Section: Discussionsupporting
confidence: 82%
“…Initial mRNA expression profiling showed that cathepsins B, L, S, D, and K were expressed in all samples with no significant differences between wildtype and P2X 7 R 2/2 BMDM preparations, with cathepsin K being weakly expressed in all cases. Cathepsin E was highly expressed in human, but not mouse macrophages as previously reported (33), and the neutrophil-specific cathepsin G was absent in all samples (Fig. 1B).…”
Section: Resultssupporting
confidence: 58%
“…Cathepsin E is an endosomal proteinase, expressed in some epithelial and hematopoietic cells, which has a role in lysosomal function and intracellular trafficking. 159 In mice, cathepsin E is expressed in the gastric epithelium as well as lymphocytes, dendritic cells, erythrocytes, and certain subsets of macrophages. 9,28,182,185 Macrophages in mice with inactivating mutations in cathepsin E (Ctse) have impaired chemotaxis and cell adhesion.…”
Section: 98mentioning
confidence: 99%
“…159 C57BL/6 mice have been noted to respond poorly to certain antigens, and their relative deficiencies in cathepsin E may contribute to these findings, although restriction in MCH class II isotypes as well as other factors is likely also important. 159 Immune responses involving this cathepsin may be expected to be blunted in mice backcrossed in the C57BL/6 versus those backcrossed to 129, BALB/c, and other mouse strains.…”
mentioning
confidence: 99%